Exploiting Social Relations for Efficient Routing in Delay Tolerant Network Environment - Patil, Ajit S; Kulkarni, Prakash J (International Journal of Computer Sciences and Engineering, 2025)
DTN is subclass of mobile ad hoc network (MANET) where instantaneous end-to-end connectivity is not available in source and destination nodes. Nodes in DTN are sparsely distributed. Frequent disconnections along with limited resources make routing in DTN more challenging. This paper proposes two routing protocols. One is Buddy Router with Time Window, which exploits social relations to maximize delivery probability. Another variant presented is Buddy Router with Replication, where controlled replication approach is used, along with social metric for message forwarding. Detailed formulation of proposed work, along with comparative analysis, based on simulations is presented. The paper also presents impact of buffer size variation and TTL variation on routing performance of different routing protocols.